Perbandingan Perumusan Tindak Pidana Incest Menurut Kuhp (UU No 1 Tahun 2023) Indonesia Dengan Malaysia Penal Code - Siti Januhairiyah Hasyim; Desy Sofiana (Jurnal Hukum dan Sosial Politik, 2023)
The purpose of writing this article is to compare the arrangements for the crime of incest under the Indonesian Criminal Code and the Malaysian Penal Code Act. The comparison includes the similarities, differences and advantages and disadvantages of each of these laws and regulations. The sources of legal materials used are primary and secondary legal materials. The data collections uses literature study techniques and data analysis. Based on a comparison of the arrangements for the crime of incest under the Indonesian Criminal Code and the Malaysian Penal Code Act, there are several similarities, differences, advantages and disadvantages of each of these arrangements. So from this comparison we can find several advantages of the Malaysian Penal Code Act, there are several similarities, differences, advantages and disadvantages of each of these arrangements. So from this comparison we can find several advantages of the Malaysian Penal Code Act regulations regarding the crime of incest which can be input for the renewal of Indonesian Criminal Code regulations. That way, the regulation of incest crimes in Indonesia will be better.